RASCAN type radar image resolution enhancement for non-metallic landmine detection (2013)
Category 3. This paper presents two resolution enhancement techniques applied to images of buried landmines acquired using a RASCAN radar, a holographic radar that is used mainly for sounding structural components of buildings, although it can be used to find buried objects too. The first technique is a phase-driven spatially variant regularization, and the second one is a wavelet-based image interpolation.